Probing cellular microenvironments and tissue remodeling by atomic force microscopy - Ludwig, Thomas; Kirmse, Robert; Schwarz, Ulrich S. (Pflügers Archiv, 2007)
The function of cells is strongly determined by the properties of their extracellular microenvironment. Biophysical parameters like environmental stiffness and fiber orientation in the surrounding matrix are important determinants of cell adhesion and migration. Processes like tissue maintenance, wound repair, cancer cell invasion, and morphogenesis depend critically on the ability of cells to actively sense and remodel their surroundings. Pericellular proteolytic activity and adaptation of migration tactics to the environment are strategies to achieve this aim. Little is known about the distinct regulatory mechanisms that are involved in these processes. The system’s critical biophysical and biochemical determinants are well accessible by atomic force microscopy (AFM), a unique tool for functional, nanoscale probing and morphometric, high-resolution imaging of processes in live cells. This review highlights common principles of tissue remodeling and focuses on application examples of different AFM techniques, for example elasticity mapping, the combination of AFM and fluorescence microscopy, the morphometric imaging of proteolytic activity, and force spectroscopy applications of single molecules or individual cells. To achieve a more complete understanding of the processes underlying the interaction of cells with their environments, the combination of AFM force spectroscopy experiments will be essential.